Radiofrequency Ablation for Chronic Posterior Sacroiliac Joint Complex Pain: A Comprehensive Review. (23rd July 2021) - Yang, Aaron J; Wagner, Graham; Burnham, Taylor; McCormick, Zachary L; Schneider, Byron J
Abstract: Radiofrequency ablation of the sacral lateral branches targets the innervation of the posterior sacroiliac ligaments and posterior portion of the sacroiliac joint. These structures are also collectively referred to as the posterior sacroiliac joint complex. This review will discuss current diagnostic block paradigms and selection criteria for sacral lateral branch radiofrequency ablation, varying techniques and technologies utilized for sacral lateral branch radiofrequency ablation, and updates on the clinical outcome literature. The current evidence suggests that sacral lateral branch radiofrequency ablation can provide relief for posterior sacroiliac joint complex pain, but the literature is limited by variability in selection criteria, the specific nerves targeted by radiofrequency ablation, and the types of radiofrequency ablation technology and techniques utilized in clinical outcome studies.